2017
DOI: 10.5812/semj.14201
|View full text |Cite
|
Sign up to set email alerts
|

Health Recommendations for the Elderly in the Viewpoint of Traditional Persian Medicine

Abstract: Background: Old age is one of the most important and longest periods of life in human beings. Identifying the effective factors in maintaining and promoting health in the elderly can prevent chronic diseases in this age group. Objective: This study aimed at presenting traditional Persian medicine (TPM) measures for maintaining the elderly's health. Methods: This review article was conducted on traditional Persian medicine textbooks and Noor software to investigate the viewpoints of Iranian and Islamic scholars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Therefore, diagnosis and treatment of the diseases in TPM are considered based on personal characteristics and differences of the patients, as well as their Mizaj 40,41 . In addition, the treatment of patients in TPM begins with giving some general health recommendations with focusing on awaking and sleeping, eating and drinking, resting and the body activity, passing the wastes from the body, and psychological and mental status; then, if it is necessary, it is followed by diet recommendations, herbal and natural remedies administration, and manual therapies, such as massage, dry or wet cupping, leech therapy, etc 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, diagnosis and treatment of the diseases in TPM are considered based on personal characteristics and differences of the patients, as well as their Mizaj 40,41 . In addition, the treatment of patients in TPM begins with giving some general health recommendations with focusing on awaking and sleeping, eating and drinking, resting and the body activity, passing the wastes from the body, and psychological and mental status; then, if it is necessary, it is followed by diet recommendations, herbal and natural remedies administration, and manual therapies, such as massage, dry or wet cupping, leech therapy, etc 42,43 …”
Section: Discussionmentioning
confidence: 99%
“…In terms of the PM approach, age is a variable that affects temperament, as a result, we selected the young age group to control for this effect on temperament (41)(42)(43)(44). Unlike the middle-aged and elderly, young people are hot-wet (45).…”
Section: Discussionmentioning
confidence: 99%
“…They are usually quick-witted and, concurrently, irascible individuals. People with wet and cold-wet temperament brains, on the contrary, react slowly to stimuli and are usually more tolerant and, concurrently, slower in sensory perception (21,23). Amrai et al found a positive relation between spiritual intelligence and conscientiousness, agreeableness, and extroversion.…”
Section: Discussionmentioning
confidence: 99%